Thesis Writing Model of Art Practice - Indro Moerdisuroso; Zaitun Y.A. Kherid (IJCAS (International Journal of Creative and Arts Studies), 2020)
ABSTRACT The result of this study is contributed to improving the academic thinking of art practice students, especially in the writing of the undergraduate thesis. The problem is about a system of academic thinking as reflected in the thesis guidebook. Students' academic thinking in thesis writing is guided by a manual book published by a local institution. The case in this study is the thesis guidebook of art practice in an art study program. In this book has no explicit explanation on method and analysis aspects. Whereas both of these aspects are precisely the essence of academic thinking, that is research-based thinking. This fact encourages a study of thesis writing model of art practice, particularly on methods and analysis aspects. This study implements a Research and Development (R&D) approach and mixed methods. The model will propose Teikmanis' typology of art-related research, such as practice-led research, research-led practice, and artistic research. It also adapted Barrett's structure of art education, which consisted of conceptual, operational and synthesis aspects. The conclusion of the study showed that the participants were able to arrange a thesis based on this model. Model Penulisan Tesis Praktik Seni ABSTRAK Hasil penelitian ini dikontribusikan untuk meningkatkan pemikiran akademik mahasiswa praktik seni, khususnya dalam penulisan skripsi. Masalahnya adalah tentang berpikir akademis sebagaimana tercermin dalam pedoman skripsi. Pemikiran akademis dalam penulisan skripsi dipandu oleh pedoman penulisan yang diterbitkan oleh institusi terkait. Kasus dalam penelitian ini adalah suatu pedoman skripsi praktik seni dalam suatu program studi seni rupa. Dalam buku ini tidak ada penjelasan eksplisit tentang aspek metode dan analisis. Padahal kedua aspek ini justru merupakan inti dari pemikiran akademis, yaitu pemikiran berbasis penelitian. Fakta ini mendorong studi model penulisan skripsi praktik seni, terutama dalam aspek metode dan analisis. Studi ini menerapkan pendekatan Penelitian dan Pengembangan (R&D) dengan metode campuran. Model ini mengusulkan tipologi penelitian seni Teikmanis, seperti practiceled research, research-led practice, dan artistic research. Selain itu juga mengadaptasi struktur pendidikan seni Barrett, yang terdiri dari aspek konseptual, operasional, dan sintesis. Kesimpulan dari penelitian ini menunjukkan bahwa para partisipan dapat menyusun skripsi berdasarkan model ini.